'Holding on' and 'letting go': a thematic analysis of Australian parent's styles of coping with their adult child's methamphetamine use. (3rd July 2020) - Maltman, Kelly; Savic, Michael; Manning, Victoria; Dilkes-Frayne, Ella; Carter, Adrian; Lubman, Dan I.
Abstract: Background: Although it is well established that parents can be negatively impacted by their child's methamphetamine use, there is little research on how parents cope. This study aimed to explore the coping styles of Australian parents contacting an online counselling service concerned about their adult child's methamphetamine use. Method: A thematic analysis of online counselling transcripts was used to examine key coping styles employed by parents ( n  = 26) who were seeking support in relation to their adult child's methamphetamine use. Results: Two primary coping styles were identified. Parents were 'holding on' by trying to control and change their adult child's methamphetamine use in order to improve the adult child's circumstances and their own; or they were 'letting go' by releasing control to their adult child in the hope that over time they would reduce their drug consumption or seek help. While 'holding on' had benefits in terms of parents feeling as though they had some power to change their adult child's situation, it also involved considerable ongoing stress and strain. 'Letting go' was often a source of grief, but for some parents, it enabled them to focus on self-care and their own wellbeing. Conclusion: This study highlights the potential value of treatment services tailoring the support they provide based on parents coping styles and preferences.